Analisis Pengaruh Kualitas Pelayanan Administrasi Layanan Publik terhadap Kepuasan Masyarakat di Kantor Desa Slorok, Kecamatan Garum, Kabupaten Blitar - Novela Kriswi Wega Agustia; Novita Setyoningrum; Novi Catur Muspita (Lembaga Pengembangan Kinerja Dosen, 2025)
Public satisfaction is the result of comparing their expectations of the services received with the quality of performance or service provided. The method used in this study is descriptive quantitative. The aim is to determine the effect of public service quality on public satisfaction, identify obstacles that arise during service delivery, and provide solutions to overcome these obstacles at the Slorok Village Office, Garum District, Blitar Regency. This study indicates that public service quality has an effect on public satisfaction with a value of 0.204 or 20.4%, while the remaining 79.6% is influenced by other variables outside this study.